SBPar scanning: Toward a complete optimal skeleton scan strategy for Additive Manufacturing (Statistics, Optimization & Information Computing, 2025)
In a previous work (Prog Addit Manuf 6:93–118, 2021), a novel Additive Manufacturing scan strategy was designed; the Skeleton-Based Perpendicular (SBP) scanning should show minimal trajectory series compared to classical exiting hatching patterns used in the literature. In contrast, this pattern should lead to mechanical anisotropy due to the one-way oriented printing if it is applied in all part’s layers; a complementary scan strategy must be designed to balance the SBP orientations. This important constraint led the author of this paper to develop the “Skeleton-Based Parallel” (SBPar) strategy as a SBP’s complementary scan for avoiding such issues. Subsequently, the present work details the design of the SBPar pattern and the corresponding scan length; analytical formulations are drawn-up for a simple rectangle as a proof of the concept. Therefore, the superposition of SBP and SBPar constitutes the total skeletal scanning (SB). Results emphasized two conflictual interests: apart from stripe scan, the proposed SBPar scan exhibits a maximized trajectory compared to the other scan strategies; thus, it seems lastly compromising the minimization objective targeted by SBP scan. On the other hand, according to this maximization aspect, the second interest is regarded in terms of surface control which requires maximizing matter spreading and thereafter offering higher densification to the processed surfaces. Furthermore, The SB and the classical scan strategies showed degrees of length-similarities according to decision variables adopted herein. Further works will be dedicated to the implementation of the Skeletal-Based trajectory within real 3D-parts and then to the associated mechanical characterization.